Perillyl Alcohol Protects Against Fe-NTA-Induced Nephrotoxicity and Early Tumor Promotional Events in Rat Experimental Model - Jahangir, Tamanna (Oxford University Press, 2007)
Plants have been widely used as protective agents against a wide variety of processes and compounds that damage tissues via free radical mechanisms. Perillyl alcohol (PA) is a naturally occurring monoterpene found in the essential oils of numerous species of plants including mints, cherries and celery seeds. This monocyclic monoterpene has shown antioxidant and therapeutic activity in various studies against various xenobiotics. In this study, we have analyzed the effects of PA against single intraperitoneal dose of ferric nitrilotriacetate (Fe-NTA) (9 mg iron per kg body weight)-induced nephrotoxicity and early tumor promotional events. The pretreatment of Fe-NTA-treated rats with 0.5% per kg body weight dose and 1% per kg body weight dose of PA for seven consecutive days significantly reversed the Fe-NTA-induced malondialdehyde formation, xanthine oxidase activity (P < 0.001), ornithine decarboxylase activity (P < 0.001) and (3)[H]thymidine incorporation in renal DNA (P < 0.001) with simultaneous significant depletion in serum toxicity markers blood urea nitrogen and creatinine (P < 0.001). Significant restoration at both the doses was recorded in depleted renal glutathione content, and its dependent enzymes with prophylactic treatment of PA. Present results suggest that PA potentially attenuates against Fe-NTA-induced oxidative damage and tumor promotional events that preclude its development as a future drug to avert the free radical-induced toxicity.